Development of the Logistics 4.0 Concept in the Digital Economy - Trushkina, N.; Dzwigol, H.; Serhieieva, O.; Shkrygun, Yu. (Економічний вісник Донбасу, 2020)
The transition to a digital economy is becoming a key driver of GDP growth. This is due not only to the effect obtained from the automation of existing processes, but also from the introduction of new, breakthrough business models and technologies, including digital platforms, digital ecosystems, in-depth analytics of big data, Industry 4.0, Logistics 4.0.
At the same time, digital transformation is seen as a radical change in the complex of business processes, from product development to customer service, as well as the introduction of modern digital technologies in the organization of business processes in enterprises.
The purpose of the article is to analysis the features and trends of organizing logistics activities in the context of digital transformation of business processes; research of the main prerequisites for the formation of the Logistics 4.0 concept; determination of priority directions for its further development in the context of Industry 4.0.
Based on the generalization of scientific approaches, the definition of the concept of "Logistics 4.0" has been clarified, which means the modern paradigm of managing logistic (material, financial, information, transport) flows and organizing a complex of logistics activities (purchase and delivery of material resources, warehousing, production, stock formation, recycling of industrial waste, customer service, transportation and sale of finished products) using breakthrough digital technologies and information systems.
The priority areas of organizing the logistics activities of enterprises using digital technologies include the following: multichannel logistics; logistics marketplaces; rethinking the use of packaging; mass personalization; Silver Economy (new services for older clients and new opportunities for older workers); sustainable logistics; sharing economy; multi-supply; customer experience; smart containerization; big data analytics; augmented and virtual reality; cloud service applications and APIs; Internet of Things; robotics and automation; new generation wireless communication; blockchain; Artificial Intelligence; unmanned aerial vehicles or "drones"; 3D printing; unmanned vehicles; quantum computing; supergrid logistics; space logistics; the use of digital platforms that unite customers and transport and logistics companies (the parties can enter into digital contracts, exchange transport booking requests and electronic documents, control the delivery of goods in real time).
All this can help to reduce costs by optimizing procurement; decrease in personnel costs and decrease in labour costs as a result of automation; reduction of errors in logistics; optimization of the supply process; efficient warehouse management; forecasting shipments; creation of optimal routes; operational planning of loads and control of delivery times; ensuring product delivery on time, improving customer loyalty; optimal interaction with customers on the "last mile". Перехід до цифрової економіки стає ключовим чинником зростання ВВП. Це обумовлено не тільки ефектом, одержуваних від автоматизації існуючих процесів, а й від впровадження нових, проривних бізнес-моделей і технологій, серед яких цифрові платформи, цифрові екосистеми, поглиблена аналітика великих масивів даних, технології «Індустрія 4.0», «Логістика 4.0».
При цьому цифрова трансформація розглядається як радикальні зміни комплексу бізнес-процесів, починаючи від розробки продукції і закінчуючи обслуговуванням споживачів, а також впровадження сучасних цифрових технологій при організації бізнес-процесів на підприємствах.
Метою статті є аналіз особливостей і тенденцій організації логістичної діяльності в умовах цифрової трансформації бізнес-процесів; дослідження основних передумов становлення концепції Логістика 4.0; визначення пріоритетних напрямів її подальшого розвитку в контексті Індустрія 4.0.
На основі узагальнення наукових підходів уточнено визначення поняття «Логістика 4.0», під яким розуміється сучасна парадигма управління логістичними (матеріальними, фінансовими, інформаційними, транс¬портними) потоками й організації комплексу процесів логістичної діяльності (закупівля та доставка матеріальних ресурсів, складування, виробництво, формування запасів, рециклинг промислових відходів, обслуговування споживачів, транспортування і збут готової продукції) із застосуванням проривних цифрових технологій та інформаційних систем.
До пріоритетних напрямів організації логістичної діяльності підприємств з використанням цифрових технологій можна віднести такі: мультиканальна логістика; логістичні маркетплейси; переосмислення використання упаковки; масова персоналізація; «Срібна економіка» (нові послуги для літніх клієнтів і нові можливості для немолодих працівників); стала логістика; економіка спільного використання; мультипостачання; клієнтський досвід; розумна контейнеризація; аналітика великих даних; доповнена і віртуальна реальність; хмарні сервісні програми та інтерфейси прикладного програмування; Інтернет речей; робототехніка й автоматизація; бездротовий зв'язок нового покоління; блокчейн; штучний інтелект; безпілотні літальні апарати або «дрони»; 3D друк; безпілотні автомобілі; квантові обчислення; логістика супермережі; космічна логістика; використання цифрових платформ, які поєднують замовників і транспортно-логістичні компанії (сторони можуть укладати цифрові контракти, обмінюватися заявками на бронювання транспорту та електронними документами, контролювати доставку вантажів в режимі реального часу).
Все це може сприяти скороченню витрат за рахунок оптимізації закупівель; зниженню витрат на персонал і зменшенню трудовитрат у результаті автоматизації; зменшенню помилок у логістиці; оптимізації процесу поставок; ефективному управлінню складами; прогнозуванню відвантажень; створенню оптимальних маршрутів; оперативному плануванню завантажень і контролю термінів доставки; забезпеченню доставки продукції вчасно, покращуючи клієнтську лояльність; оптимальній взаємодії з клієнтами на «останній милі». Переход к цифровой экономике становится ключевым фактором роста ВВП. Это обусловлено не только эффектом, получаемым от автоматизации существующих процессов, но и от внедрения новых, прорывных бизнес-моделей и технологий, среди которых цифровые платформы, цифровые экосистемы, углублённая аналитика больших массивов данных, технологии «Индустрия 4.0», «Логистика 4.0».
При этом цифровая трансформация рассматривается как радикальные изменения комплекса бизнес-процессов, начиная от разработки продукции и заканчивая обслуживанием потребителей, а также внедрение современных цифровых технологий при организации бизнес-процессов на предприятиях.
Целью статьи является анализ особенностей и тенденций организации логистической деятельности в условиях цифровой трансформации бизнес-процессов; исследование основных предпосылок становления концепции Логистика 4.0; определение приоритетных направлений ее дальнейшего развития в контексте Индустрия 4.0.
На основе обобщения научных подходов уточнено определение понятия «Логистика 4.0», под которым понимается современная парадигма управления логистическими (материальными, финансовыми, информационными, транспортными) потоками и организации комплекса процессов логистической деятельности (закупка и доставка материальных ресурсов, складирование, производство, формирование запасов, рециклинг промышленных отходов, обслуживание потребителей, транспортировка и сбыт готовой продукции) с применением прорывных цифровых технологий и информационных систем.
К приоритетным направлениям организации логистической деятельности предприятий с использованием цифровых технологий можно отнести такие: мультиканальная логистика; логистические маркетплейсы; переосмысление использования упаковки; массовая персонализация; «серебряная экономика» (новые услуги для пожилых клиентов и новые возможности для немолодых работников); устойчивая логис¬тика; экономика совместного использования; мультиснабжение; клиентский опыт; умная контейнеризация; аналитика больших данных; дополненная и виртуальная реальность; облачные сервисные приложения и интерфейсы прикладного программирования; Интернет вещей; робототехника и автоматизация; беспроводная связь нового поколения; блокчейн; искусственный интеллект; беспилотные летательные аппараты или «дроны»; 3D печать; беспилотные автомобили; квантовые вычисления; логистика суперсетей; космическая логистика; использование цифровых платформ, которые объединяют заказчиков и транспортно-логистические компании (стороны могут заключать цифровые контракты, обмениваться заявками на бронирование транспорта и электронными документами, контролировать доставку грузов в режиме реального времени).
Все это может способствовать сокращению затрат за счёт оптимизации закупок; снижению затрат на персонал и уменьшение трудозатрат в результате автоматизации; уменьшению ошибок в логистике; оптимизации процесса поставок; эффективному управлению складами; прогнозированию отгрузок; созданию оптимальных маршрутов; оперативному планированию загрузок и контролю сроков доставки; обеспечению доставки продукции вовремя, улучшая клиентскую лояльность; оптимальному взаимодействию с клиентами на «последней миле».